Soil types create different rhizosphere ecosystems and profoundly affect the growth characteristics of ratoon sugarcane - Xiaoming Wang; Junjun Ma; Chaoxian Fang; Jinghuan Zhu; Shilong Wang; Zuli Yang (Frontiers in Microbiology, 2025)
IntroductionRhizosphere ecological factors play a crucial role in the soil feedback function of ratoon sugarcane. However, limited information exists regarding the differences and relationships among these factors across various soil types (sandy, loam, and clay) and their impact on sugarcane growth and yield characteristics. This study aims to address this knowledge gap by investigating the rhizosphere ecological dynamics of ratoon sugarcane in different soil types.MethodsA combination of biochemical experiments and high-throughput sequencing was employed to analyze the rhizosphere ecological factors of ratoon sugarcane. The study examined biochemical function- and enzymatic activity-related factors in the rhizosphere soil, as well as the microbial community composition and their relationships with sugarcane growth and yield characteristics.ResultsBiochemical function- and enzymatic activity-related factors in the rhizosphere soil were generally positively correlated with each other and with sugarcane growth characteristics. For instance, soil respiration and soil catalase activity showed significant positive correlations with theoretical sugarcane yield (correlation coefficients of 0.773, p < 0.05 and 0.863, p < 0.01, respectively). Symbiotic relationships were observed between the rhizosphere soil microbial and root system endophyte communities. Functional differences in microbial communities among different soil types were significant (p < 0.05), indicating that soil type strongly influences the functional expression of rhizosphere soil microbial communities. The abundance of bacteria and fungi in the ratoon sugarcane rhizosphere soil was negatively and positively correlated with most soil biochemical functions, respectively. Additionally, correlations existed between the abundance of endophytic bacteria and fungi in the root system and sugarcane yield. Eleven soil biochemical and functional factors were positively correlated with theoretical sugarcane yield and theoretical sugar yield indicators.DiscussionOur findings suggest that different feedback directions and correlation strengths exist between sugarcane growth characteristics and various ecological factors in their rhizosphere across different soil types and spatial scales. These results provide insights into the complex interactions between sugarcane and its rhizosphere environment, highlighting the importance of soil type in shaping these interactions. The study offers guidance for improving soil microbial community structure to enhance sugarcane growth and yield, serving as a valuable reference for soil management in sugarcane fields.